ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CAPITAL ADEQUACY RATIO PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009-2013 - Tatik Kurniyati, 11.05.52.0048; Suwarti, Titiek (Students Journal of Accounting and Banking, 2015)
This study aims to analyze the effect of Return On Asset, Non Performing Loan and Loan to Deposit Ratio of Capital Adequacy Ratio Banking companies listed on the Indonesia Stock Exchange. Population in this study are the financial statements of banking companies in Indonesia, published by the Stock Exchange during the period 2009-2013. The technique of collecting samples in this study using purposive sampling method which samples are teken based on the criteria used by the researchers. Samples taken as many as 22 commercials banks in 2009-2013. The result showed that Return On Asset have negative significant, Non Performing Loan have negative not significant, and Loan to Deposit Ratio have negative not significant to Capital Adequacy Ratio. Keywords: ROA, NPL, LDR, and CAR